NORM INEQUALITIES FOR POSITIVE ELEMENTARY OPERATORS AND ENTANGLEMENT OF STATES - Okelo, N B; ONGATI, OMOLO; KARIEKO, OBOGI ROBERT (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
We present norm inequalities for positive elementary operators vi- a Cauchy-Schwarz inequality and Minkowskis inequality techniques. Norm inequalities are presented in Euclidean algebras linked to Minkows-ki's light cones. Lastly, we explore the applications in quantum theoryparticularly in entanglement of states.